Implementation of the science e-module based on guided inquiry with the flipped classroom strategy to improve students science process skills - Risca Cornelia Katauhi; Wahono Widodo; Dhita Ayu Permata Sari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aims to determine the influence of implementing a science e-module based on guided inquiry with the flipped classroom strategy to improve junior high school students' science process skills. The research used is pre-experimental with one group pretest-posttest research design to determine the improvement of students' science process skills in one group without any comparison group. The research sample is grade eight junior high school students at SMP Gresik, Indonesia, with a total of 30 students that consist of 15 males and 15 females. The research instruments used are tests (pretest-posttest), observation (students' activity sheets), and survey (students' response questionnaire). The data collection techniques used are written, observation, and survey methods. The results of the tests are analyzed using the N-Gain calculation, which obtained 0.66, which is included in the medium category. The result of the observational analysis towards the improvement of science process skills has a very good category with a percentage of 94.8%. Meanwhile, the student response survey analysis has an average presentation of 96.7% in the very good category. The results of this study indicate that implementing a science e-module based on guided inquiry with the flipped classroom strategy can effectively improve junior high school students' science process skills.